The effectiveness of constraints-led training on skill development in interceptive sports: A systematic review - Clark, M. E.; McEwan, K.; Christie, C. J. (International Journal of Sports Science & Coaching, 2019)
There has been a recent increase in constraints-led training to assist the development of technical and cognitive skill in sports. While the benefits of constraints-led training appear obvious, the evidence for this type of training is not clear. Therefore, a systematic review of the literature was conducted to establish the effectiveness of this approach to training within interceptive sports. Four databases (Google Scholar, JURN, Mendeley and Science Direct) were searched for journal articles focused on skill acquisition within interceptive sports. A methodological and reporting quality assessment was done to determine the quality of each article. Eighteen articles were selected for review. The results of these two quality assessments revealed poor quality scores for the majority of the studies. However, 77.7% of the studies found a positive effect in skill acquisition following manipulation in training protocol; therefore, the implementation of the constraints-led approach within interceptive sport can be advocated. Key methodological structures were identified as well as aspects of methodology that should be avoided to ensure reliable results for future studies. Further research is required to determine the effectiveness of constraints-led training on interceptive sporting performance.